Modelling of parametric kinetic ion-acoustic instability in helicon discharge - Olshansky, V.V. (Вопросы атомной науки и техники, 2015)
A computer simulation of the development of the parametric kinetic ion-acoustic instability is carried out for the helicon discharge conditions by the "particle in cell" method. Linear and nonlinear stages of the ion-acoustic instability and turbulence are investigated for the typical parameters of the helicon plasma. It is shown that the high efficiency of the helicon plasma sources can relate to development of both short and long wavelength kinetic ion-acoustic parametric instabilities and the turbulent heating of electrons and ions caused by the ion-acoustic turbulence can be one of the dominant mechanisms of the pumping wave energy absorption in the helicon plasma. Методом "particle in cell" проведено моделирование развития параметрической кинетической ионно-звуковой неустойчивости в условиях геликонного разряда. Исследованы линейная и нелинейная стадии ионно-звуковой неустойчивости и турбулентности при типичных значениях параметров геликонной плазмы. Показано, что высокая эффективность геликонных источников плазмы может быть связана с развитием как коротковолновой, так и длинноволновой кинетической ионно-звуковой неустойчивости, и турбулентный нагрев электронов и ионов, обусловленный ионно-звуковой турбулентностью, может быть одним из доминирующих механизмов поглощения энергии волны накачки в геликонной плазме. Методом "particle in cell" проведено моделювання розвитку параметричної кінетичної іонно-звукової нестійкості в умовах геліконного розряду. Досліджені лінійна і нелінійна стадії іонно-звукової нестійкості і турбулентності при типових значеннях параметрів геліконної плазми. Показано, що висока ефективність геліконних джерел плазми може бути пов'язана з розвитком як короткохвильової, так і довгохвильової кінетичної іонно-звукової нестійкості, і турбулентне нагрівання електронів та іонів, зумовлене іонно-звуковою турбулентністю, може бути одним з домінуючих механізмів поглинання енергії хвилі накачки в геліконній плазмі.